Will bangladesh seize or squander the economic opportunity offered by the demographic dividend? - Rafiqul Huda Chaudhury (Asia-Pacific Population Journal, 2012)
Bangladesh experienced a significant reduction in fertility and mortality during the last three decades of the twentieth century, leading to a drastic change in the population structure. To date, the number of persons in productive ages by far exceeds the number in dependent ages. This creates a one-time opportunity to boost economic growth. The present paper examines the extent to which Bangladesh has taken advantage of this window of opportunity. It also identifies remaining challenges to exploiting this opportunity to further increase economic growth and development. The paper concludes that in order to reap benefits from this window of opportunity, Bangladesh must make critical investments in its human capital base, as well as improve infrastructure and the overall investment climate.